The study of DNA dynamics on glassy carbon electrode surfaces - Perera, D. M. H. Kaushalya (Kansas State University, 2014)
The potential-dependent reorientation dynamics of double stranded DNA (ds-DNA) covalently attached to planar glassy carbon electrode (GCE) surfaces were studied in this thesis. The orientation of ds-DNA was investigated via the distance-dependent quenching of fluorescence from a 6–carboxyfluorescein (FAM6) flurophore to the electrode surface. The fluorophore was covalently bound to the distal end of the DNA. Fluorescence microscopy was employed for optical detection of FAM6 fluorescence and hence the DNA dynamics. The variation of the fluorescence from the dye with electrode potential is attributed to distance-dependent dipole-electrode energy transfer. Application of positive potentials (i.e., +0.2 V vs. open circuit potential, OCP) to the GCE caused the ds-DNA to align approximately parallel to the surface, yielding strong FAM6-electrode energy transfer and low fluorescence intensity. With the switching of the potential towards negative values (i.e., -0.4 V vs. OCP) the ds-DNA realigned perpendicular to the GCE surface leading to a reduction in energy transfer and high fluorescence intensity. Initial DNA reorientation upon a change in electrode potential is very fast. These fast dynamics have been observed and characterized in a number of previous publications. We have observed subsequent slow dynamics that we attribute to slow orientational relaxation of the DNA. Our observations were first reported by Q. Li, et al., J. Am. Chem. Soc. 2012, 134, 14467. In this thesis, this prior work is extended to verify the reproducibility of these new dynamics and to eliminate the possibility of certain artifacts as their source. Specifically, the experiments are repeated using a new cell design and a different buffer. In the primary experiments performed in this thesis, the dependence of the DNA reorientation dynamics on surface coverage was investigated by observing the fluorescence modulation as a function of probe concentration in the functionalization bath. Concentrations of 0.25, 1.0 and 1.5 µM 35-mer ds-DNA were employed. Electrodes functionalized at these concentrations have ds-DNA surface coverages of 1.18 x 10[superscript]12, 3.24 x 10[superscript]12 and 4.26 x 10[superscript]12 cm[superscript]-2, respectively. With increasing concentration of the DNA probe, the reorientation time constant at positive applied bias (vs. OCP) increased, indicting reorientation was slowed. In contrast, the time constant decreased with the negative applied bias (vs. OCP) indicating faster orientational relaxation. The possible origins for the observed trends in the reorientation time constant are discussed.
Keywords: DNA dynamics; Chemistry (0485); Physical Chemistry (0494)